Relative age and specific learning disorder diagnoses: A Finnish population-based cohort study - Arrhenius Bianca; Gyllenberg David; Vuori Miika; Tiiri Elina; Lempinen Lotta; Sourander Andre (United Kingdom, 2022)
Background
Being among the youngest in class has previously been associated with attention-deficit/hyperactivity disorder (ADHD) and academic disadvantage, but the relative age effect on learning disorders is less well understood. This study examined whether relatively young children are more likely to be diagnosed with specific learning disorders than their older peers.
Methods
The setting included all 388,650 children born singleton in Finland from 1996 to 2002. Cases diagnosed with specific learning disorders in specialized health care by the age of 10 were identified from national registers. Cumulative incidences of specific learning disorders and the corresponding incidence rate ratios (IRRs) and 95% confidence intervals (CIs) were calculated for each birth month compared to January.
Results
During follow-up, 3162 (0.8% of 388,650) children were diagnosed with a specific learning disorder. Children born in December displayed higher cumulative incidences for specific learning disorders than children born in January (IRR: 1.77, 95% CI: 1.50–2.11). The findings were similar for girls (IRR: 2.01, 1.44–2.83) and boys (IRR: 1.70, 1.39–2.08). ADHD did not explain the association, as the IRR for the youngest children with specific learning disorders and ADHD was 1.59 (1.13–2.26) compared to those without ADHD (IRR: 1.84, 1.51–2.24).
Conclusions
Relatively younger children in Finnish schools were more likely to be diagnosed with a specific learning disorder by the age of 10. Increased awareness of how relative age differences affect the likelihood for children to be diagnosed with specific learning disorders is needed among parents, clinicians, and teachers.